A European economic policy in the making: Success with modest means - Peter Becker (Stiftung Wissenschaft und Politik (SWP), 2020)
Although the roots of the European Union lie in economic integration, the EU's economic policy competences and possibilities are narrowly limited in European primary law. Nevertheless, the influence of the EU, and in particular the European Commission, on economic policies of the member states is clearly visible and tangible. The focus of European economic policy is on the coordination of member state policies by the European Commission. It uses strategic planning instruments such as 10-year strategies, guidelines, and reform recommendations, which it bundles within the European Semester. European economic policy-makers are actually faced with the task of limiting the acute socio-economic consequences of the Covid-19 pandemic on the one hand, and finding answers to the structural challenges posed by globalisation, digitisation, and climate change on the other. A common European economic policy is becoming increasingly necessary, and expectations are growing. The European Commission is trying to combine these two tasks - the stimulation of the European economy and the sustainable transformation of national economies - with the new European recovery fund "Next Generation EU". The European Green Deal will become the guiding principle for both economic policy coordination and economic policy at the national level. This reorientation of European economic policy towards sustainable and decarbonised growth will promote the Europeanisation and, in the long term, the unitarisation of national economic policies
Keywords: 320; Europäische Union; Europäische Integration; Gemeinsame Wirtschaftspolitik von Staaten/Staatengruppen; Europäischer Binnenmarkt; Steuerung/Regulierung; Wirtschaftsplanung; Koordinationsmechanismen (Wirtschaft); Wirtschaftspolitische Konzeption; Wirtschaftsstruktureller Wandel; Green New Deal; Unitarismus; Entwicklungsperspektive und -tendenz; Wirtschaftsverfassung; Soziale Marktwirtschaft; Wirtschaftsprozess; Wettbewerbsrecht; Industriepolitik; Wirtschaftsförderung; Europäisches Semester